Current Population Survey, October 2010: School Enrollment and Internet Use Supplement ([Verlag nicht ermittelbar], 2011)
This data collection is comprised of responses from two sets of survey questionnaires, the basic Current Population Survey (CPS) and a survey on the topics of School Enrollment and Internet Use in the United States, which was administered as a supplement to the 2010 October CPS. The Census Bureau and the National Center for Education Statistics jointly sponsored the supplemental questions for October. The CPS, administered monthly, is a labor force survey providing current estimates of the economic status and activities of the population of the United States, for the week prior to the survey. Specifically, the CPS provides estimates of total employment (both farm and nonfarm), nonfarm self-employed persons, domestics, and unpaid helpers in nonfarm family enterprises, wage and salaried employees, and estimates of total unemployment. The October 2010 supplemental survey queried respondents on school enrollment for all persons in the household aged three years and over. Supplement data includes information collected on current grade at public or private school, whether currently attending college full- or part-time at a two- or four-year institution, year last attended a regular school, year graduated from high school, grade retention, and whether any business, vocational, technical, trade, or correspondence courses were ever taken. Respondents were also queried on Internet and computer use, particularly if members of the household use the Internet, and how access to the Internet is obtained. Demographic variables include age, sex, race, Hispanic origin, marital status, veteran status, educational attainment, occupation, and income.